BIOMARKERS OF THE ALLERGIC INFLAMMATION AS ADDITIONAL CRITERIA FOR THE ASTHMA CONTROL - L.M. Ogorodova; D.V. Kozyritskaya; I.A. Deev; Yu.A. Petrovskaya; A.V. Ekimovskikh (Union of pediatricians of Russia, 2006)
The authors have carried on a prospective open comparative study within the parallel groups to assess the dynamics of the markers of the inflammation among the patients with various degree of bronchial asthma severity against the background of the anti-inflammatory therapy and define the role of nitrogen oxide in respiratory condensate as a biomarker during the bronchial asthma. All the patients (n = 54) have undergone determination of the bronchial hypere activity level, nitrite level in respiratory condensate, relative number of eosinophiles of nasal secretion against the background of the anti-inflammatory basic therapy application adequate to the degree of bronchial asthma severity. the researchers have revealed that application of the anti-inflammatory basic therapy adequate to the degree of bronchial asthma severity led to achievement of the criteria for the control over bronchial asthma symptoms among the majority of patients already towards the end of the 12th week. Nevertheless, the accurate reduction of biomarkers of allergic inflammation was registered only in the end of the treatment period (24 weeks). Thus, the application of the anti-inflammatory basic therapy adequate to the degree of bronchial asthma severity is necessary within no less than 24 weeks. It helps to achieve the control over symptoms of the disease, as well as it is accompanied by the accurate reduction of biomarkers of atopic inflammation, and there? Fore, it leads to the activity reduction of the respiratory tract inflammation. Biomarkers may be used not only for the purpose to assess the inflammation of the respiratory passages, but also as a marker for the asthma therapy effectiveness, which can allow optimizing the bronchial asthma therapy among children.Key words: bronchial asthma, children, atopic inflammation, bio-markers, nitrogen oxide, eosinophiles, bronchial hyperreactivity.